ASSEMBLER EDU E-MODULES: IMPROVING ARGUMENTATION SKILLS, PERSEVERANCE, AND CURIOSITY IN PHYSICS LEARNING - Astalini, Astalini; Darmaji, Darmaji; Kurniawan, Dwi Agus; Octavia, Sri Wina (Jurnal Ilmiah Ilmu Terapan Universitas Jambi, 2024)
This study examined the impact of Assembler Edu-based e-modules on enhancing students' argumentation skills, perseverance, and curiosity in high school physics learning. Employing a quantitative ex-post facto design, the research utilized a 4-point Likert scale questionnaire to gather data. Descriptive and inferential statistical methods, including simple linear regression, were used for analysis. The findings reveal that using Assembler Edu-based e-modules significantly positively affected students' argumentation skills, with a 42.2% influence. Moreover, student responses indicated a 47.6% improvement in perseverance, while curiosity in learning renewable energy topics increased by 47.4%. These results highlight the considerable potential of integrating digital tools like Assembler Edu into the learning environment. This study introduces an innovative approach to physics education by incorporating interactive e-modules based on the Assembler Edu platform. Unlike traditional learning materials, these e-modules foster a more dynamic and engaging learning experience, enhancing students' critical thinking, perseverance, and curiosity. The research adds a fresh dimension to the existing literature by demonstrating how digital technology in science education can significantly improve core skills necessary for 21st-century learners. The study's implications suggest that integrating Assembler Edu-based e-modules into the school curriculum can enrich students' learning experiences, promote a deeper understanding of complex topics like renewable energy, and cultivate essential skills such as argumentation and perseverance, which are vital for success in both academic and real-world contexts.